Fabrication and testing of Micro Electro Mechanical Systems (MEMS) flow sensors - Yeo, Eric Gim Boon. (2013)
This report illustrates the design, fabrication and experimental results of a liquid crystal polymer (LCP) membrane pressure sensor for air flow and air direction applications. The LCP proves to be a material which is more sensitive and reliable when used in MEMS. Due to its physical and chemical properties, it enables operations in harsh environment such as wind flow monitoring. Simple and low cost fabrication scheme has been developed, using only low temperature. The main features of the sensor developed in this report is to coat a thin film gold on the LCP membrane. The sensor demonstrates good sensitivity of 3.695mV and good accuracy with only up to 3.6% of error. This sensor is calibrated and tested in a wind tunnel, exposing to different wind velocity. With the experimental results obtained, it is able to show that the sensor has the ability to determine wind velocity and wind direction. It proves to be applicable to many areas today such as wind monitoring and function as a human breathing monitoring system.